The influence of transactional leadership style on employees’ innovation ability - Zhao, Wei; Sun, Xi Ming (Nurture, 2024)
Purpose: This study delves into two mainland Chinese footwear manufacturing companies to understand the link between transactional leadership and employee creativity, focusing on the mediating role of psychological empowerment. Design/Methodology/Approach: Employing descriptive statistical analysis, reliability analysis, confirmatory factor analysis, correlation analysis, and regression analysis, the study collected 576 valid questionnaires. Data analysis was conducted using SPSS 25 and Analysis of Moment Structures statistical software. Findings: Results confirm that psychological empowerment positively influences employee creativity. Transactional leadership also has a significant positive impact. Notably, psychological empowerment partially mediates the relationship between transactional leadership and creativity. Conclusions: Both transactional leadership and psychological empowerment are key factors in enhancing employee creativity, particularly in the two Chinese private footwear companies studied. Research Limitations: The research focuses on large and medium-sized firms from two Chinese regions, excluding smaller entities. Several potential influencing factors for creativity still need to be addressed. Practical Implications: Business leaders are advised to possess professional, solid skills, ensure fair treatment of employees, and provide appropriate rewards. Such practices can bolster team cohesion, spur innovation, and support sustainable enterprise growth. Contribution to literature: This work underscores the influence of psychological empowerment and transactional leadership on creativity, shedding light on the former’s mediating role. The findings enrich the literature and offer a foundation for future research in similar domains.